Design and Development of an Android-Based Application for Employee Leave and Absence Management at the Faculty of Science and Engineering, Bangka Belitung University - Yulita, Ulpa; Arkan, Fardhan; Kurniawan, Rudy (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2026)
The process of submitting leave and absence management for employees of the Faculty of Science and Engineering, Bangka Belitung University, is still carried out manually using paper forms, potentially causing delays in information, recording errors, and difficulties in data archiving. This study aims to design and implement an Android- and web-based leave and absence management application system to improve the efficiency of personnel administration. The system development method used includes the stages of needs analysis, system design, implementation, and testing. The Android application was developed using Flutter, while the web-based system uses PHP with a MySQL database and Application Programming Interface (API) integration for real-time data measurement. This system provides features for submitting leave and permits, application history, verification and approval stages by superiors, employee data management, and application status notifications. The results of functional testing indicate that most features run according to system requirements, although there is one date logic validation test that does not meet expectations. Overall, the system developed is able to improve the efficiency of the administrative process, minimize recording errors, and support more structured, transparent, and integrated personnel data management.